MEDIA INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 PADA MACAM-MACAM SEGITIGA DI KELAS IV SEKOLAH DASAR - Fitra Ramadhan; Salmaini Salmaini; Masniladevi; Gita Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A preliminary study conducted in three elementary schools in Region 1 of Tanjung Sani revealed that mathematics learning was still less interactive, and the use of digital learning media had not been optimized, resulting in limited student engagement during the learning process. This study aimed to develop an interactive learning media based on Articulate Storyline 3 for the topic of types of triangles in Grade IV elementary school that meets the criteria of validity, practicality, and effectiveness. This study employed the Research and Development (R&D) method using the ADDIE Development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects included expert validators, fourth-grade teachers, and fourth-grade students from three elementary schools in Region 1 of Tanjung Sani. The research instruments consisted of validation sheets, practicality questionnaires, and learning achievement tests. The results indicated that the developed media achieved an average validity score of 90% (very valid), an average practicality score of 85.33% (very practical), and an N-Gain score of 81.74% (high category). These findings demonstrate that the Articulate Storyline 3-based learning media is feasible for use as an innovative digital learning medium to support mathematics learning on the topic of types of triangles for fourth-grade elementary school students. Keywords: ADDIE, Articulate Storyline 3, triangles ABSTRAK Studi pendahuluan di tiga sekolah dasar wilayah 1 Tanjung Sani menunjukkan bahwa pembelajaran Matematika masih kurang interaktif dan pemanfaatan media pembelajaran digital belum optimal sehingga berdampak pada rendahnya keaktifan murid dalam proses pembelajaran. Penelitian ini bertujuan mengembangkan media pembelajaran interaktif berbasis Articulate Storyline 3 pada materi macam-macam segitiga di kelas IV sekolah dasar yang memenuhi kriteria valid, praktis, dan efektif. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE yang meliputi tahap Analysis, Design, Development, Implementation, dan Evaluation. Subjek penelitian melibatkan validator ahli, guru kelas IV, dan murid kelas IV di tiga sekolah dasar wilayah 1 Tanjung Sani. Instrumen penelitian meliputi lembar validasi, angket kepraktisan, dan tes hasil belajar. Hasil penelitian menunjukkan bahwa media yang dikembangkan memperoleh rata-rata validitas sebesar 90% dengan kategori sangat valid, rata-rata kepraktisan sebesar 94,58% dengan kategori sangat praktis, serta nilai N-Gain sebesar 81,74% dengan kategori tinggi. Berdasarkan hasil tersebut, media pembelajaran berbasis Articulate Storyline 3 layak digunakan sebagai alternatif media pembelajaran digital pada materi macam-macam segitiga di kelas IV sekolah dasar. Kata kunci: ADDIE, Articulate Storyline 3, Segitiga